Implementasi Modul Ajar Berdiferensiasi Berdasarkan Gaya Belajar Siswa SMP Kelas VII - Syadidah, Pratama Fitri; Sa'dijah, Cholis; Sudirman, Sudirman (BRILIANT: Jurnal Riset dan Konseptual, 2024)
Differentiated learning based on student learning styles is implemented to accommodate the diverse ways students process and represent information. Differentiated teaching modules are essential to align learning with teacher planning. An educational report from a school in East Java indicated a need for improvements in innovative teaching practices, learning processes, and reflective teaching. This study aims to describe the implementation process of differentiated teaching modules for Grade 7 students. A qualitative descriptive method was used, employing observation sheets to monitor teacher and student activities. Observations were conducted by two Mathematics Education-trained observers, with data converted to scores using a four-point Likert scale and analyzed qualitatively through comments and suggestions. Challenges included students’ limited ability to operate laptops, experience with group learning, confidence in sharing opinions, and careful reading of instructions. Results indicated that the differentiated teaching modules were highly effective, showing excellent ratings in both teacher and student activities across four learning sessions.